'While we can, we will': Exploring food choice and dietary behaviour amongst independent older Australians. Issue 5 (24th May 2016) - Host, Alison; Mcmahon, Anne‐Therese; Walton, Karen; Charlton, Karen
Abstract: Aim: Burgeoning proportions of populations aged over 65 years impose an increased financial burden upon governments for the provision of associated health and aged‐care services. Strategies are therefore required to mitigate service demand through the preservation of good health and independence into old age. Nutrition has been acknowledged as a key factor for realisation of this goal. The objective of the present study was to investigate factors responsible for shaping food shopping, cooking and eating behaviours amongst healthy, independently living Australians aged 60 years and over. Methods: Eighteen (5 male, 13 female) independently living residents sourced from three low‐care Illawarra Retirement Trust (IRT) lifestyle residential facilities volunteered to take part in the present study. All participants were aged 60 years or more and in relatively good health. Semi‐structured focus groups were implemented to explore factors influencing the selection, acquisition and preparation of food. Each session was digitally recorded, transcribed verbatim and subsequently examined using content and thematic analysis. Results: Ten sub‐themes were identified and grouped into three broader themes: adaptation, psychosocial parameters and food landscape. Findings reflect an active self‐determination to retain independence, with a focus on the maintenance of favourable nutritional status. A sense of resourcefulness was evident through the development of strategies to overcome potential barriers to healthy eating. Conclusions: Factors that influence the food choices of community‐living older Australians are complex and multifactorial, and underpinned by a strong desire for independence and control over personal health outcomes. Studies involving larger, more demographically diverse participant groups are required to elicit socially acceptable strategies that will empower older Australians to sustain their health and independence for the longer term.